Clip‐off Chemistry: Synthesis by Programmed Disassembly of Reticular Materials. (25th November 2021) - Yang, Yunhui; Broto‐Ribas, Anna; Ortín‐Rubio, Borja; Imaz, Inhar; Gándara, Felipe; Carné‐Sánchez, Arnau; Guillerm, Vincent; Jurado, Sergio; Busqué, Félix; Juanhuix, Judith; Maspoch, Daniel
Abstract: Bond breaking is an essential process in chemical transformations and the ability of researchers to strategically dictate which bonds in a given system will be broken translates to greater synthetic control. Here, we report extending the concept of selective bond breaking to reticular materials in a new synthetic approach that we call Clip‐off Chemistry. We show that bond‐breaking in these structures can be controlled at the molecular level; is periodic, quantitative, and selective; is effective in reactions performed in either solid or liquid phases; and can occur in a single‐crystal‐to‐single‐crystal fashion involving the entire bulk precursor sample. We validate Clip‐off Chemistry by synthesizing two topologically distinct 3D metal‐organic frameworks (MOFs) from two reported 3D MOFs, and a metal‐organic macrocycle from metal‐organic polyhedra (MOP). Clip‐off Chemistry opens the door to the programmed disassembly of reticular materials and thus to the design and synthesis of new molecules and materials. Abstract : Clip‐off Chemistry, a new approach to synthesizing molecules and materials based on the programmed de‐reticulation and controlled etching at the molecular level in reticular materials, is introduced. Using this strategy, we have transformed two 3D metal‐organic frameworks (MOFs) into two topologically distinct 3D MOFs, and one metal‐organic polyhedra into a metal‐organic macrocycle.